Success Factors in Preventing Violence Against Students in Educational Institutions - วิจิตรวรรณา สมถวิล; สำเภาทอง อรุณี (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 15, 2025)
Youth are important for developing the country’s competitive potential. Accumulating knowledge, experience and skills, as well as molding personalities, attitudes, morality and ethics for youth are therefore important. However, the current situation of youth students in a more complex social context affects youth behavior and safety. News about violence between groups of friends in educational institutions and bullying in educational institutions have been international problems for many years. This article aims to study the types of violence, causes and success factors in preventing violence against students in educational institutions. Many studies confirm that bullying in educational institutions does not only affect students, but also affects the effectiveness of the education system, the emotional well-being of society, and the increasing violence in society. In summary, violence against students in educational institutions is an act that causes damage to students by school staff, other students or other persons not related to the school. Violence can be classified into 3 types: physical, mental and sexual violence. The causes are various factors: family vulnerability, peer problems, community problems, easy access to inappropriate information sources, and drug use. The important success factors in preventing violence against students in educational institutions include strong administrators and implementation of a strong policy framework to deal with violence against children, cooperation between the education sector, diverse networks and partners, and the availability of information on violence and bullying in educational institutions. Participation of stakeholders in the school community.